The Law Of Removing Watermarks On Short Videos According To The Perspective Of Wahbah Az Zuhaili (Case Study Of Remove Watermark Tiktok Application) - Pradana, Rio; Iwan, Iwan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Cases of removing watermarks on creative videos on Tiktok often harm content creators because the videos are taken unfairly. Researchers identified a problem in this that was found to be a short video from TikTok that was uploaded back to TikTok and other platforms without including a watermark where the watermark was a sign of protection of intellectual property rights of the original video owner. This research uses research methods Normative legal research or library research is research that examines document studies using various secondary data such as laws and regulations, court decisions, legal theories, and can be in the form of scholars' opinions. The form of loss felt by the content creator himself to the exploration of his videos without watermarks is certainly the most detrimental to the identity of his work and the economic value that makes the content creator himself decrease his income. Not only that, but actually the Copyright Law has carried out legal protection for content creators whose videos are deliberately removed watermarks on the video. Wahbah Zuhaili himself views the case as a form of idea theft and can be subject to civil and administrative sanctions. In this case Wahbah Zuhaili himself is in line with copyright law.